Structural, thermal, optical and dielectric studies of Dy3+: B2O3-ZnO-PbO-Na2O-CaO glasses for white LEDs application - Mohammed, Al-B. F. A.; Lakshminarayana, G.; Baki, S. O.; Halimah, M. K.; Kityk, I. V.; Mahdi, M. A. (Elsevier, 2017)
Dy3+-doped borate glasses with nominal composition (60-x) B2O3-10 ZnO-10 PbO-10 Na2O-10 CaO-(x) Dy2O3 (x = 0, 0.1, 0.2, 0.5, 0.75, 1.0, 1.5 and 2.0 mol%) were prepared by the melt quenching technique. The XRD and SEM confirm the amorphous nature of the glasses and through EDAX, all the related elements were found in the synthesized glasses. The vibrations of metal cations such as Pb2+ and Zn2+, B–O–B bond bending vibrations from pentaborate groups, bending vibrations of BO3 triangles, and stretching vibrations of tetrahedral BO4− units etc. are identified from the respective FTIR and Raman spectra including the non-hygroscopic nature of the synthesized glasses. The TGA and DSC measurements were performed to study thermal properties, where ΔT >100 °C (ΔT = Tx – Tg) for all the glasses. Among all the Dy3+-doped glasses, the 0.75 mol% Dy3+-doped glass shows the highest PL intensity with four emissions, where the two transitions corresponding to 4F9/2 → 6H15/2 (blue) and 4F9/2 → 6H13/2 (yellow) are observed more intense than the others. The CIE chromaticity (x,y) coordinates for BZPNCDy 0.1 mol% glass are (0.398, 0.430), close to the white light region in the CIE 1931 chromaticity diagram. The dielectric properties of the 0.75 mol% Dy3+-doped glass such as dielectric constant, dielectric loss and AC conductivity were studied in the various frequencies and temperature.